Efektivitas Pendekatan Pembelajaran Matematika Realistik dengan Karakter Nggusuwaru Terhadap Hasil Belajar Matematika Siswa SD - Dusalan, Dusalan; Sowanto, Sowanto (Program Studi Pendidikan Matematika, 2023)
The development of students' mathematical knowledge can be carried out through meaningful integration of mathematics education and nggusuwaru character values ​​to grow students' abilities, develop cultural values ​​with nggusuwaru characters according to the current context and use a basis for mathematical creative thinking skills. The aim of this research is how effective the Realistic Learning Approach with the Nggusuwaru Character is on the Mathematics Learning Outcomes of Students at SDN Inpres Kalo Pai. This type of research is quasi/quasi-experimental research, the sampling technique in this research is Porposive Sampling by considering class VI students at SDN Inpres. If there is only 1 (one) class of 30 people. Based on the results of data analysis, it shows that the average value is 70.59 in the high category, the normality test results are 0.200 - 0.05, with a normal distribution, the homogeneity test results show that a value of 0.451 > 0.05 is obtained, so the two variants are the same, next The results of hypothesis testing show that tcount > ttable (3.285 > 2.048), with the criteria that H0 is rejected and H1 is accepted. So it can be concluded that there is effectiveness of a realistic learning approach with the nggusuwaru character on the mathematics learning outcomes of class VI students at SDN Inpres Kalo Pai.